2018
DOI: 10.1002/oa.2678
|View full text |Cite
|
Sign up to set email alerts
|

Isotopes and new norms: Investigating the emergence of early modern U.K. breastfeeding practices at St. Nicholas Kirk, Aberdeen

Abstract: In this study, we aim to extend the chronological, geographical, and societal scope of previous bioarchaeological research on infant diet and age at weaning in Britain in the past through the analysis of the large medieval and post‐medieval skeletal assemblage from St. Nicholas Kirk, Aberdeen, Scotland. Stable carbon and nitrogen isotope data were obtained from rib collagen from 67 sub‐adults across the two phases and were compared with mean adult female dietary isotope values. Nitrogen isotope data were model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 59 publications
(140 reference statements)
1
20
0
1
Order By: Relevance
“…This fits well with elsewhere in Medieval Europe in terms of historical documents (Fildes 1986) and isotopic studies (e.g. see Britton et al 2018 for a review of UK populations).…”
Section: Historic Foodways: Transition Culture and Religionsupporting
confidence: 89%
“…This fits well with elsewhere in Medieval Europe in terms of historical documents (Fildes 1986) and isotopic studies (e.g. see Britton et al 2018 for a review of UK populations).…”
Section: Historic Foodways: Transition Culture and Religionsupporting
confidence: 89%
“…Historical demographic studies have revealed that during the 18th–19th century, big merchants developed in Osaka (where SKT871 locates) and lower status groups were employed as residential employees, but commerce was carried out by a large number of small family merchants in Edo (where Hitotsubashi is located) during the same period (Saito, , ). Evidence from modern (Dennis, ; Saadeh et al, ; WHO, ) and historical European (Britton et al, ; Fildes, ; but see Nitsch, Humphrey, & Hedges, ) human populations indicates that maternal employment outside the home leads to a lower age at the end of weaning. Because Sakai City was a merchants’ city and was located within Osaka, most lower status people in Sakai City, including women, might be employees of big merchants, and so the weaning process ended earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Scotland (Britton et al, 2018). By comparison, a far smaller number of studies have employed oxygen isotope analysis to investigate breastfeeding practices and determine weaning age in past societies.…”
Section: Breastfeeding and Weaning Practicesmentioning
confidence: 99%